2020
DOI: 10.1101/2020.01.28.920488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Only ten percent of the global terrestrial protected area network is connected via intact land

Abstract: Land free of direct anthropogenic disturbance is considered essential for achieving biodiversity conservation outcomes but is rapidly eroding. In response, many nations are increasing their protected area estates but little consideration is given to the context of the surrounding landscape. This is despite the fact that connectivity between protected areas is critical in a changing climate 5 and mandated in international protected area targets. By utilizing the latest human pressure assessment, which shows tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…S2). For example, we found that PAI, used to assess functional connectivity, varied considerably among countries that were assigned a connectivity value of zero by the ConnIntact indicator 9 , which is used to assess the contiguity of intact natural land between PAs irrespective of animal movement (i.e., structural connectivity) (Fig. 2).…”
Section: Protected Area Isolationmentioning
confidence: 99%
See 4 more Smart Citations
“…S2). For example, we found that PAI, used to assess functional connectivity, varied considerably among countries that were assigned a connectivity value of zero by the ConnIntact indicator 9 , which is used to assess the contiguity of intact natural land between PAs irrespective of animal movement (i.e., structural connectivity) (Fig. 2).…”
Section: Protected Area Isolationmentioning
confidence: 99%
“…We identified concentrated flows using MMP grid cells in the 90th percentile, hereafter referred to as critical connectivity areas (CCAs). We further divided CCAs into two categories based on a threshold HFI value of 4 previously used by others 9,11,31 : "modified" CCAs where HFI ≥ 4, and "intact" CCAs where HFI < 4. We found that 97% of CCAs occur in intact areas and 3% are modified (i.e., 9.7% and 0.3% of the terrestrial realm, respectively).…”
Section: Global Connectivity Conservation Prioritiesmentioning
confidence: 99%
See 3 more Smart Citations